A study of the impact of new technology and teaching methodologies on global maritime education and training into the 21st century - Muirhead, Peter Maxwell Pilley (Curtin University, 2002)
Global maritime education and training (MET) is currently subject to great change brought about by new international legislation, a dynamic shipping environment, the growing impact of technology, and the challenges maritime institutions face to survive in an uncertain market place.The aim of the research is to determine to what extent global MET institutions can enhance and enrich traditional practices through access to new technology and the use of innovative teaching and assessment methods' within a sustainable and achievable framework.The first Chapters of the study investigate the impact of change on the global MET scene by examining how international maritime legislation influences activities of maritime institutions. Ninety institutions from fifty-three countries responded to a survey that examines their intentions regarding the use of satellite communications, Information Technology, computing, multimedia, simulation and distance learning delivery methods. Shipboard operations that impact upon future training needs are also put under the spotlight.The study analyses the potential use of the Internet, e-mail, simulation and distance education services to determine how these elements can be used to advantage for the education and training of seafarers. An evaluation is made of the use of computers and marine simulators as assessment tools, in the light of international concerns about standards of competence.The study concludes that maritime institutions can benefit from the use of new technology, but only through rational planning and sustainable staged growth. A series of continua of technical development are provided to assist institutions, from to the largest, to plan for technical development and growth in a rational way.